Optimizing the Mutiara Pagi Program to Strengthen Character and Islamic Literacy at RRI Pro 1 Kediri - Rohmah Istikomah; Mirzza 'Aliyatul Abroroh (Simfoni Ilmu Cindekia, 2026)
The Mutiara Pagi Study Program is a form of community service implemented through a collaboration between the Islamic Educational Management Study Program of STAI Ma'had Aly Al Hikam Malang and RRI Pro 1 Kediri. The program aims to provide contextual Islamic education through radio broadcasting to strengthen community character, spirituality, and Islamic literacy. This community service employed a descriptive qualitative approach, with data collected through observation, documentation, and content analysis of the study materials delivered across eight broadcast sessions from January to June 2026. Data were analyzed using the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that the topics presented are including emotional management from an Islamic perspective, maintaining istiqamah in the use of social media, seeking blessings during the dawn (Subuh) hours, reflecting on the values of Ramadan, stress management based on Islamic teachings, the broader meaning of sustenance (rizq), the value of qana'ah (contentment), and character education within the family effectively addressed various contemporary social issues in a practical and relevant manner. Delivering these topics through radio broadcasts contributed to enhancing public understanding of Islamic teachings, strengthening religious values, fostering self-control, cultivating gratitude, and increasing awareness of the essential role of the family in character development.